Size distribution and ion composition of aerosol collected at Ny-Ålesund in the spring–summer field campaign 2013 - Giardi, F; Becagli, S; Traversi, R; Frosini, D; Severi, M; Caiazzo, L; Ancillotti, C; Cappelletti, D; Moroni, B; Grotti, M; Bazzano, A; Lupi, A; et al. (Rendiconti Lincei, 2016)
During the 2013 Arctic campaign, direct measurements and size-segregated samplings of atmospheric aerosol were carried out from March to September at the Gruvebadet observatory in Ny-Ålesund (78°56′N, 11°56′E; Svalbard Islands). Continuous size distribution measurements (104 size classes) were performed both in the nano- (TSI-SMPS system) and micro-metric (TSI-APS device) range with a resolution of 10 min. Aerosol sampling was carried out on daily basis (PM10 fraction, 00:01–23:59 UTC) and with a 4-day resolution (four-stage cascade impactor). A back-trajectory analysis was performed for specific events to understand transport processes and possible source areas of aerosol reaching Ny-Ålesund. Aerosol samples were analyzed for ion composition (inorganic cations and anions, selected organic anions) by a three-chromatograph system after extraction in ultra-sonic bath. Special attention was spent in identifying and interpreting the seasonal pattern of natural and anthropic chemical markers. Sea spray aerosol was evenly distributed along all the sampling period with maxima related to wind speed. Its size distribution peaks in 1.0–2.5 or 2.5–10 μm, depending on the transport conditions and distance from source areas. Anthropic sulfate dominates the spring aerosol load (Arctic Haze), both in acidic form (H2SO4) and in partially or totally neutralized ammonium salts. Biogenic contributions, marked by methanesulfonic acid, are relatively relevant in late spring–early summer and are distributed in the finest aerosol fraction (<1.0 μm).